Book Review: Bhangya Bhukya, The Roots of the Periphery: A History of the Gonds of Deccan India. Issue 2 (August 2017) - Nathan, Dev
Bhangya Bhukya, The Roots of the Periphery: A History of the Gonds of Deccan India . New Delhi: Oxford University Press, 2017, ₹750, xvii + 209 pp. ISBN: 978-0-19-946808-9.